Correlation between atopic eczema, total eosinophil counts and serum IgE - A case-control study (Panacea Journal of Medical Sciences, 2025)
Background: Atopic eczema (AE) is a pruritic, chronically relapsing inflammatory skin condition and its prevalence is increasing globally. Researchers have convincingly correlated severity of AE with hemato-immunological abnormalities due to the complex interaction between genetic susceptibility genes and heightened immunological response.Aim and Objective: (a) To determine association between severity of atopic eczema and total eosinophil counts. (b) To determine association between severity of atopic eczema and total serum IgE levels. (c) To determine association between total eosinophil counts and total serum IgE Levels in atopic eczema.Materials and Methods: This was a case-control study conducted in the Department of Dermatology - OPD, Karnataka Institute of Medical Sciences, Hubballi, Karnataka. A total of 80 subjects were examined, 50 being AE cases (33 males & 17 females) and 30 age matched controls (20 males & 10 females).Study subjects underwent clinical evaluation and relevant investigations. SCORAD index, Serum IgE and Absolute Eosinophil Count (AEC) in both the groups.Results: Increased serum IgE, AEC were more frequently observed with AE patients than in control group. There exists a positive correlation between IgE, AEC and SCORAD in AE cases than in controls. The degree of correlation between SCORAD index and serum IgE is significantly positive (r =0.66, p<0.01) in cases than in controls and this correlation is higher than that between Serum IgE and AEC.Conclusion: The study results may conclude that the SCORAD index can be used as a cutaneous marker of hemato-immunological abnormalities. In resource poor circumstances SCORAD index can be used as a substitute for expensive blood investigation and may guide to select a proper, more effective therapeutic modality.